Effect of sodium dodecyl sulphate and polyoxyethylene dodecyl ether on the rheological behaviour and stability of natural rubber latex - Lim, Hui Mei; Misran, Misni (Akademi Sains Malaysia, 2018)
Surfactants are important class of material used in latexes to impart stability at the solid/liquid interface. Ionic surfactants and nonionic surfactants are known to provide elec- trostatic and steric stabilisation. In this study, two surfactants having chain length of twelve hydrocarbons were added to the natural rubber latex (NRL) respectively to determine its zeta potential values, adsorption isotherm and rheological properties. Previous study has shown that optimum stability was observed when the alkyl chain of surfactant contains twelve car- bon atoms. The zeta potential magnitude of NRL in the presence of sodium dodecyl sulphate increased as the surfactant concentration increases, while polyoxyethylene dodecyl ether did not show a significant change in zeta potential. The isotherms were of Langmuir Type 1, the amount of surfactant adsorbed per unit area at the plateau region was 6.0 × 10-6 mol m-2 for sodium dodecyl sulphate and 2.1 × 10-6 mol m-2 for polyoxyethylene dodecyl ether. The elastic modulus and relative viscosity of the NRL suspensions increased significantly in the presence of sodium dodecyl sulphate and also with polyoxyethylene dodecyl ether as compared to the NRL system due to stronger colloidal forces. The maximum packing volume fractions of the NRL stabilised with sodium dodecyl sulphate and polyoxyethylene dodecyl ether were found to be lower than NRL itself.